Study of the petrology of the shale rock from the Parana basin (Brazilian Journal of Radiation Sciences, 2021)
In the present work, the characteristics of the shale rock, collected in the surrounds of Limeira, in the interior of São Paulo, were studied. Shales are mostly fine granules, susceptible to the mineralogical rearrangement, and their chemical composition is quite varied due to the geomorphology and the tectonism undergone by the sedimentary basins. They are impermeable structures, formed by the consolidation of layered clay with thin laminations. Because of these characteristics presented, together with the decline of petroleum production, a growing interest in a better understanding and knowledge of the physical-chemical properties of the shale rocks inner is observed.  In this work, the gamma-ray computed industrial tomography technique was established to be used in the characterization of the shale samples. The results were validated using those obtained by conventional methodologies, such as scanning electron microscopy (SEM), x-ray fluorescence and x-ray diffraction. Several characteristics have been studied, such as the analysis of the particle morphology, the contrasts and distributions of these particles in the internal structure of the rock, identification of the types of elements present (quantitative analysis), as well as establishing the proportion of each element present in the mineral through its crystalline structure, with images of the rock internal structure.